2011
DOI: 10.1681/asn.2011010038
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of CSF-1 Isoforms in Lupus Nephritis

Abstract: Colony-stimulating factor-1 (CSF-1), the principal growth factor for macrophages, is increased in the kidney, serum, and urine of patients with lupus nephritis, and eliminating CSF-1 suppresses lupus in MRL-Fas lpr mice. CSF-1 has three biologically active isoforms: a membrane-spanning cell surface glycoprotein (csCSF-1), a secreted proteoglycan (spCSF-1), and a secreted glycoprotein (sgCSF-1); the role of each isoform in the circulation and kidney in autoimmune disease is not well understood. Here, we constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…While ischemia-induced IL-34 drives AKI and thereby worsens subsequent CKD, our prior studies (4) and others (24,25) indicate that CSF-1 hastens AKI repair after I/R. However, CSF-1 mediates repair in AKI and conversely escalates spontaneous (MRL-Fas lpr lupus nephritis) (3,5,7,8,20) and induced (unilateral ureteral obstruction) (22,23) CKD. This divergent role of CSF-1 is analogous to epidermal growth-factor receptor signaling in AKI and CKD.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…While ischemia-induced IL-34 drives AKI and thereby worsens subsequent CKD, our prior studies (4) and others (24,25) indicate that CSF-1 hastens AKI repair after I/R. However, CSF-1 mediates repair in AKI and conversely escalates spontaneous (MRL-Fas lpr lupus nephritis) (3,5,7,8,20) and induced (unilateral ureteral obstruction) (22,23) CKD. This divergent role of CSF-1 is analogous to epidermal growth-factor receptor signaling in AKI and CKD.…”
Section: Discussionmentioning
confidence: 77%
“…As Mø mediate kidney repair and destruction, we reasoned that the principal molecule required for Mø survival, proliferation, and activation -CSF-1 -is central to regulating the fate of the kidney. Our prior studies show that CSF-1 expression is beneficial in kidneys destined to repair (4) and, conversely, harmful in kidneys destined for autoimmunemediated chronic disease (3,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These human data show incomplete suppression of circulating monocytes under the conditions in this study, which may have contributed to the lack of efficacy observed in lesional sites. Regarding suppression of local M-CSF activity, there are three homodimeric isoforms of the M-CSF ligand, which have specific spatial and temporal expression resulting in unique functional activities [38]. Although the epitope for PD-0360324 is contained within the N-terminal 146 amino acid region of M-CSF, which is conserved in all isoforms (data not shown), we cannot rule out the potential for differences in tissue penetration or pharmacokinetic requirements for suppression of each isoform in vivo.…”
Section: Cd16mentioning
confidence: 99%
“…3,34 Macrophages propagate kidney injury through secretion of inflammatory cytokines, production of profibrotic growth factors, and generation of reactive oxygen species. [35][36][37] Macrophage depletion attenuated fibrosis in a unilateral ureteral obstruction (UUO) model of injury, suggesting that macrophage infiltration may be deleterious.…”
Section: Monocytes Macrophages and Dendritic Cellsmentioning
confidence: 99%